Tracing High-z Galaxies in X-Rays with JWST and Chandra - Aidan J. Kaminsky; Nico Cappelluti; Günther Hasinger; Alessandro Peca; Caitlin M. Casey; Giulia Cerini; Nicole E. Drakos; Andreas Faisst; Ghassem Gozaliasl; Olivier Ilbert; Jeyhan S. Kartaltepe; Alexander Kashlinsky; et al. (The Astrophysical Journal)
We leverage James Webb Space Telescope (JWST) data from the COSMOS-Web survey in order to provide updated measurements on the auto-power spectrum of the now resolved cosmic near-infrared background (CIB) and its coherence with the unresolved soft cosmic X-ray background (CXB) observed by Chandra at z > 6. Maps of the CIB in the F277W and F444W NIRCam filters are constructed with sources fainter than m _AB = 25 and cross-correlated with the CXB in the [0.5–2] keV band. We find that on scales between 1″ and 1000″ the CIB–CXB cross-power in both NIRCam filters is statistically significant, with signal-to-noise ratios (S/Ns) of 4.80 and 6.20, respectively, from redshifts 0 ≤ z ≤ 13. In our high- z (6 ≤ z ≤ 13) interval we find coherence in both filters, with S/Ns of 7.32 and 5.39, respectively. These results suggest that there are X-ray-emitting galaxies resolved by JWST, including star-forming galaxies and active galactic nuclei. We fit the large-scale biasing of the IR sources producing the CIB as a function of z with results consistent with prior measurements, and place constraints on the CXB flux and biasing at low and high z . The CXB flux measurements presented in this study suggest that approximately 94% of the [0.5–2] keV CXB is resolved, and this value is consistent within 2 σ with the complete resolution of the [0.5–2] keV CXB.